Disulfiram and its novel derivative sensitize prostate cancer cells to the growth regulatory mechanisms of the cell by re‐expressing the epigenetically repressed tumor suppressor—estrogen receptor β. Issue 11 (24th November 2015) - Sharma, Vikas; Verma, Vikas; Lal, Nand; Yadav, Santosh K.; Sarkar, Saumya; Mandalapu, Dhanaraju; Porwal, Konica; Rawat, Tara; Maikhuri, J.P.; Rajender, Singh; Sharma, V.L.; Gupta, Gopal
Abstract : Estrogen Receptor‐β (ER‐β), a tumor‐suppressor in prostate cancer, is epigenetically repressed by hypermethylation of its promoter. DNA‐methyltransferases (DNMTs), which catalyze the transfer of methyl‐groups to CpG islands of gene promoters, are overactive in cancers and can be inhibited by DNMT‐inhibitors to re‐express the tumor suppressors. The FDA‐approved nucleoside DNMT‐inhibitors like 5‐Azacytidine and 5‐Aza‐deoxycytidine carry notable concerns due to their off‐target toxicity, therefore non‐nucleoside DNMT inhibitors are desirable for prolonged epigenetic therapy. Disulfiram (DSF), an antabuse drug, inhibits DNMT and prevents proliferation of cells in prostate and other cancers, plausibly through the re‐expression of tumor suppressors like ER‐β. To increase the DNMT‐inhibitory activity of DSF, its chemical scaffold was optimized and compound‐339 was discovered as a doubly potent DSF‐derivative with similar off‐target toxicity. It potently and selectively inhibited cell proliferation of prostate cancer (PC3/DU145) cells in comparison to normal (non‐cancer) cells by promoting cell‐cycle arrest and apoptosis, accompanied with inhibition of total DNMT activity, and re‐expression of ER‐β (mRNA/protein). Bisulfite‐sequencing of ER‐β promoter revealed that compound‐339 demethylated CpG sites more efficaciously than DSF, restoring near‐normal methylation status of ER‐β promoter. Compound‐339 docked on to the MTase domain of DNMT1 with half the energy of DSF. In xenograft mice‐model, the tumor volume regressed by 24% and 50% after treatment with DSF and compound‐339, respectively, with increase in ER‐β expression. Apparently both compounds inhibit prostate cancer cell proliferation by re‐expressing the epigenetically repressed tumor‐suppressor ER‐β through inhibition of DNMT activity. Compound‐339 presents a new lead for further study as an anti‐prostate cancer agent. © 2015 Wiley Periodicals, Inc.